PENERAPAN TEKNOLOGI DIGITAL DALAM STRATEGI PEMBELAJARAN AKTIF DI PENDIDIKAN DASAR: TINJAUAN SISTEMATIS TERHADAP DAMPAK DAN EFEKTIVITAS - Wildan Nuril Ahmad Fauzi; Yuli Setiawati (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2025)
This study aims to identify the effectiveness of digital technology integration in active learning strategies in primary schools and evaluate its impact on student engagement and achievement. In addition, it also explores the challenges teachers face in implementing digital technologies in the classroom. Through the analysis of several literatures and empirical studies, it was found that digital technologies such as video conferencing apps, online learning platforms and digital smartboards play a significant role in improving student interaction, engagement and learning outcomes. Although digital technology is capable of creating an interactive and flexible learning environment, challenges such as limited infrastructure and technology skills among teachers are still the main obstacles in its implementation. Therefore, this study suggests more equitable infrastructure support, continuous teacher training and education policies that ensure equitable access to technology across regions. Thus, technology-based active learning can be optimized to improve the quality of education in primary schools.